Thoracoscopic Occlusion of the Left Atrial Appendage. Issue 3 (May 2015) - Mokracek, Ales; Kurfirst, Vojtech; Bulava, Alan; Hanis, Jiri; Tesarik, Richard; Pesl, Ladislav
Abstract : Objective: Left atrial appendage (LAA) plays a crucial role in the etiopathogenesis and the prevention of the stroke in patients with nonvalvular atrial fibrillation (AF). This paper presents our first experience with thoracoscopic LAA occlusion using an external clip. Methods: We performed a total of 30 LAA occlusions with the AtriClip from left thoracoscopy approach during the period from July 2012 to July 2013. AtriClip was implanted during the bilateral thoracoscopic radiofrequency (RF) as part of left atrial ablation procedure. Results: Among the 30 procedures, AtriClip was once periprocedurally partially positioned. In the remaining procedures, the implantation was successful without complications. Of the 30 patients, 29 underwent transesophageal echocardiography and computer tomography examination at 3 months after the procedure. Apart from the patient with the partial clip placement, a residual pouch of 18 mm was detected in another patient. In the remaining group (28/30 patients, 93%), the exclusion was complete. No migration or any other clip implantation–related complications occurred during the follow-up. None of the patients experienced an embolization event. Conclusions: Endoscopic AtriClip implantation appears to be a reproducible and safe method of LAA occlusion, with a minimal risk and a high efficiency. In our opinion, the AtriClip implantation is a reasonable part of thoracoscopic AF treatment and should be considered as an alternative tool for stroke risk reduction in patients with AF.